Health post readiness and its influence on mothers’ care-seeking practice for their sick children in Ethiopia - Mekonnen, Wassie Negash; Tiruneh, Gizachew Tadele; Birhane, Adugnaw; Mekonnen, Wubegzier (Frontiers in Public Health, 2025)
IntroductionInfection accounts for about half of all neonatal deaths and it contributes to 37% of neonatal deaths in Sub-Saharan Africa where there is low health facility readiness and the quality of service given at health facilities is low. In this study, we assessed the influence of health posts’ readiness on the care-seeking behavior of mothers of sick young children.MethodThis study analyzed data from a community-based implementation survey conducted by JSI in the two districts of Ethiopia from April 2021 to July 2022. In this study, we enrolled 4,262 and 4,081 mothers with children < 15 months at the baseline and end-line surveys, respectively, of which 508 and 359 infants were diagnosed for illness at 66 and 64 health posts at the baseline and end-line surveys. We used the Service Availability and Readiness Assessment tool to compute the facility readiness score. We used independent sample t-test and logistic regression to see the contributions of facility readiness for care-seeking practices of mothers. AOR at 95% CI and p-value < 0.05 is used to declare a statistically significant association between variables and to control the confounding.ResultsIn the end-line survey about 359 sick young infants were identified. And in the baseline survey, 508 young infants were ill. Most of 88.0% sick young infants sought care in the end line compared to 57.3% at the baseline (p < 0.001). The overall summated mean facility readiness score was 69.6%, equivalent to 49.0% of the standardized mean score. This study also highlights rich households (AOR = 2.02; 95% CI: 1.1–3.9), reaching out to health posts (HPs) equipped with materials and supplies (AOR = 1.52; 95% CI: 1.2–1.9), and ANC use (AOR = 2.35; 95%CI: 1.2–4.7) were positively associated with care seeking practice compared to their counterparts.ConclusionThe study reveals a moderate level of health post-readiness that needs improvement. Health posts readiness, ANC use, parity, and wealth status influenced the care-seeking behavior of mothers for their sick children.